A PRELIMINARY CHECKLIST OF BUTTERFLY DIVERSITY IN THE WESTERN GHATS AT POINGUINIM, CANACONA, GOA - PAGI, KARUNA; SUDHIR, OMKAR; RAO, KULKARNI RAJENDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Butterflies are the most beautiful insects. They are well adapted to the landscape and react quickly to any alteration in their habitat as a result of anthropogenic activities. Thus they act as bio- indicators. Presence of rich butterfly diversity in and around Poinguinim reflects the health of its environment; however, variations in butterfly population in different areas indicate impact of human activities. Documentation of butterfly composition should be updated regularly by researchers or NGOs as it help in estimating impact of anthropogenic activities on the habitat and also crucial to fill up any voids in the process of conservation of butterfly fauna. In the present investigation , the highest number of butterfly species was recorded from Dharwatem Forest Area (DFA) Sub site -3 ( 35 species , 160 individuals) and this might be due to presence of sufficient host plants and favorable climatic conditions like humidity and temperature for the growth and development, followed by Parshuram Temple (PT) Sub site-1 (27 species,132 individuals ), Shradhanand High School (SHS) Sub site-2 (24 species, 117 individuals) with moderate human interference and least was in Tirwan Forest Area (TFA) Sub site - 4 (17 species and 45 individuals) with maximum human activities as the survey site was adjacent to the National highway.